Establishment and Validation of Theileria annulata Sporozoite Ak-93 Infection in Laboratory-Reared Hyalomma anatolicum Tick Using In Vivo and In Vitro Assays - Asghar Afshari; Gholamreza Habibi; Mohammad Abdigoudarzi; Fereshteh Yazdani (Tehran University of Medical Sciences, 2020)
Background: Tropical Theileriosis caused by Theileria annulata is a tick-borne disease which transmitted by the ixodid tick members of the genus Hyalomma. Studies on different aspects of disease require to access infective sporozoite of parasite which produced by tick vector. This study was carried out to establish of T. annulata life cycle to achieve T. annulata infected ticks. Methods: Laboratory rabbit and calf were used for rearing of Hyalomma anatolicum different instars. Unfed nymphs were fed on T. annulata infected calf. Clinical signs, Giemsa stained smears and Polymerase Chain Reaction (PCR) methods were used for detection of infection in blood and tick specimens. Susceptible calf was used for confirmation of sporozoites maturation and infectivity in bioassay test. Results: Hyalomma anatolicum two and three-host strategies of life cycle was lasted 90 and 116 days respectively. The PCR confirmed T. annulata infection in blood and tick samples. Maturation of T. annulata sporozoites was confirmed in bioassy test. First clinical symptom of disease was seen earlier in the case of transmission of disease through feeding of live ticks in comparison with blood injection method. Conclusion: Complete life cycle of T. annulata was done and confirmed by clinical signs, microscopic examination, molecular methods and bioassay test. According to published reports to date, this is the first report of establishment of H. anatolicum tick infection with T. annulata using susceptible calf under controlled conditions in Iran.